Cooperation and Competition in the European Parliament: A Game Theoretical Interpretation - Alexandru Volacu (Romanian Journal of European Affairs)
In this paper the author analyzes the nature of the legislative process which takes place within the European Parliament by studying the bilateral interactions among its relevant decisional groups, i.e. the parliamentary groups. In this sense, the author uses a methodological approach inspired from game theory, describing these interactions in the form of non-cooperative games similar in structure and function to the “negotiator’s dilemma” model proposed by Lax and Sebenius. Through comparing at a theoretical level the optimal strategies employed by parties in national parliaments with a majority-supported government with the optimal strategies employed by groups in the European Parliament the author concludes that the level of bilateral cooperation in the EP surpasses the one existent in national legislatures as cooperation is induced through the systemic relation developed among the groups as well as through institutional and ideological factors.